Mesenteric Lipoma in a Child- A Case Report - Mozumder, Mahmudur Rahman; Afrin, Rawnak; Biswas, Tanima; Haque, Jasmine Ara; Hoque, Tanjida; Anjum, Munira; Tofa, Tasnuba Tahsin (Journal of Dhaka Medical College, 2024)
Mesenteric lipomas are very rare intraperitoneal tumors in children. When symptoms like severe abdominal pain, constipation, repeated vomiting develop, they are brought into medical attention. Despite ambiguous clinical findings, a sonographic suspicion may be further strengthened by CT scan or MRI. However, diagnostic laparotomy with resection of the mass followed by histopathological evaluation may confirm the diagnosis. We report one such rare case of a mesenteric lipoma in an 8 years old girl which may well be among the first 25 cases of mesenteric lipoma in children reported worldwide. J Dhaka Med Coll. 2022; 31(2) : 258-263